LEGAL PROTECTION FOR CHILD VICTIMS OF SEXUAL VIOLENCE BASED ON POSITIVE LAW IN INDONESIA - Tarore, Lady Lanny; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2024)
The objectives of this study: 1). to find out how legal protection for child victims of sexual violence is based on positive law in Indonesia today; 2). to find out what are the weaknesses of legal protection for child victims of sexual violence based on positive law in Indonesia today. This study uses a normative legal approach, with a descriptive analytical research method. The data used are primary and secondary data which will be analyzed qualitatively. The research problems are analyzed using the theory of legal objectives and the theory of punishment. The results of the study conclude that: 1) Legal protection for child victims of sexual violence based on positive law in Indonesia today that the context of protection for victims of crime, the existence of preventive and repressive efforts carried out, both by society and the government (through law enforcement officers), such as providing protection/supervision from various threats that can endanger the lives of victims, providing adequate medical and legal assistance, a fair examination and trial process for perpetrators of crimes, is basically one manifestation of human rights protection and a balancing instrument; 2). The weakness of legal protection for child victims of sexual violence based on positive law in Indonesia is that law enforcement officers (police, prosecutors, judges) still treat child victims of sexual violence as objects, not subjects whose legal rights must be listened to and respected. They mostly still make child victims of sexual violence a second victim (revictimization) of the case they experienced. Victims are still often blamed and not given the protection they need. The officers (police, judges, prosecutors) do not have a perspective on child victims of sexual violence.